Nora Ephron at the movies a visual celebration of the writer and director behind When Harry met Sally, You've got mail, Sleepless in Seattle, and more - Kaplan, Ilana (Abrams, 2024)
"Nora Ephron at the Movies offers an unfiltered look at Ephron as a champion of the rom-com and as a feminist Hollywood trailblazer. It explores her life and work by pairing detailed criticism with exclusive interviews with Ephron's key collaborators, including Andie MacDowell and Jenn Kaytin Robinson, to add color and nuance to her life and legacy. The women in her stories paralleled reality--the veil was lifted, the glossy sheen removed. Her protagonists share an unwavering sense of humor about life's mishaps, and they never take themselves too seriously--like Julie trying to master the art of cooking lobsters in Julie & Julia, Sally's theatrical fake orgasm in Katz's deli in When Harry Met Sally, or Rachel perfecting a key lime pie only to throw it in her cheating husband's face in Heartburn. Through her keenly self-aware humor and semi-autobiographical stories, Ephron left behind a groundbreaking legacy as a beloved journalist, essayist, screenwriter, author, producer, director, and feminist who delivered stories of resilience embedded in sharp wit and upper-crust landscapes. Through that lens, she became emblematic of rom-coms, shifting and redefining conversations around the complexities of relationships and the women who have them."